Risk of worsening heart failure and all-cause mortality following COVID-19 vaccination in patients with heart failure: a nationwide real-world safety study - Sindet-Pedersen, Caroline; Michalik, Felix; Strange, Jarl Emanuel; Christensen, Daniel Mølager; Nouhravesh, Nina; Gerds, Thomas; Andersson, Charlotte; Folke, Fredrik; Biering-Sørensen, Tor; Fosbøl, Emil; Torp-Pedersen, Christian; Gislason, Gunnar H.; et al. (Circulation. Heart failure, 2023)
BACKGROUND: Patients with heart failure are vulnerable to the SARS-CoV-2 infection. However, limited evidence exists on the safety of the SARS-CoV-2 mRNA vaccines in this patient population. The objective of this study was to investigate the risk of all-cause mortality, worsening heart failure, venous thromboembolism, and myocarditis associated with the mRNA vaccines in patients with heart failure. - METHODS: Using Danish nationwide registries, 2 cohorts were constructed: (1) all prevalent heart failure patients in 2019 aged 40 to 95 years and (2) all prevalent heart failure patients in 2021 aged 40 to 95 years, who were vaccinated with either of the 2 mRNA vaccines (BNT162B2 or mRNA-1273). The patients in the 2 cohorts were matched 1:1 using exact exposure matching on age, sex, and duration of heart failure. To estimate standardized absolute risks, outcome-specific Cox regression analyses were performed. - RESULTS: The total study population comprised 101 786 patients. The median age of the study population was 74 years (interquartile range, 66-81). The standardized risk of all-cause mortality within 90 days was 2.23% (95% CI, 2.10%-2.36%) in the vaccinated cohort and 2.56% (95% CI, 2.43%-2.70%) in the unvaccinated cohort (90-day risk difference, −0.33% [95% CI, −0.52% to −0.15%]). The standardized risk of worsening heart failure within 90 days was 1.10% (95% CI, −1.01% to 1.19%) in the 2021 (vaccinated) cohort and 1.08% (95% CI, 0.99%-1.17%) in the 2019 (unvaccinated) cohort (risk difference, 0.02% [95% CI, −0.11% to 0.15%]). No significant differences were found regarding venous thromboembolism or myocarditis. - CONCLUSIONS: Receiving an mRNA vaccine was not associated with an increased risk of worsening heart failure, myocarditis, venous thromboembolism, or all-cause mortality.